Deterrent Effect as a Punishment Goal from the Perspective of Criminal Law and Islamic Criminal Law - Muhammad Ismail; Aulia Tri Olivia; Fahri Albar Harahap (Jurnal Sahabat ISNU SU, 2024)
The implementation of criminal sanctions under Islamic law has long been a subject of legal and human rights debates in Indonesia. While Islamic criminal law is regarded by its proponents as an effective mechanism for creating a deterrent effect and maintaining public order, critics argue that some forms of punishment are inconsistent with contemporary human rights standards and Indonesia's pluralistic legal system. This study aims to examine the concept of deterrence in Islamic criminal law and analyze its effectiveness in achieving justice, legal certainty, and social welfare. The research employs a normative juridical method using a qualitative descriptive approach based on library research. Primary and secondary legal materials, including legislation, books, scientific journals, and other relevant literature, were analyzed through qualitative and inductive methods. The findings reveal that the deterrent effect in Islamic criminal law is reflected in four categories of punishment, namely ḥudūd, qiṣāṣ, kafārah, and taʿzīr, each of which serves preventive, corrective, and educational purposes. Unlike positive criminal law, which predominantly relies on imprisonment, Islamic criminal law provides differentiated sanctions according to the nature and severity of the offense. The effectiveness of these sanctions is not merely measured by the severity of punishment but by their ability to protect public interests (maṣlaḥah), uphold justice, prevent future crimes, and maintain social order. Therefore, the deterrent effect in Islamic criminal law represents a comprehensive approach that combines punishment with moral education and social protection, making it an integral component of the broader objectives of Islamic law (maqāṣid al-sharīʿah).